Comparative Performance Analysis of IaC Tools for Deploying Containerized SDN Topologies in Cloud Environments - Lima, Vitor Reiel M.; Callado, Arthur; Bonfim, Michel; Gonçalves, Enyo (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2026)
This paper presents a comparative analysis of Infrastructure as Code (IaC) tools applied to the automation of containerized Software-Defined Networking (SDN) topologies in cloud environments. The study highlights the increasing complexity of modern networks and the necessity for efficient and automated management through NetDevOps principles. It explores the capabilities of popular IaC tools, specifically Ansible and Terraform, in the provisioning and deployment of SDN topologies using Containernet and Docker. The research includes a quantitative analysis of runtime performance across network topologies (Single, Linear, and Tree) and evaluates tool efficiency in creating and destroying network scenarios. As results, we present how the tools perform in terms of execution time, providing insights into advantages and challenges associated with using different IaC tools automating emulated network environments.